2020
DOI: 10.1002/ppsc.201900441
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Highly Stable and Photoluminescent Cadmium‐Free InP/GaP/ZnS Core/Shell Quantum Dots and Application to Quantitative Immunoassay

Abstract: Indium phosphide (InP) quantum dots (QDs) are ideal substitutes for widely used cadmium‐based QDs and have great application prospects in biological fields due to their environmentally benign properties and human safety. However, the synthesis of InP core/shell QDs with biocompatibility, high quantum yield (QY), uniform particle size, and high stability is still a challenging subject. Herein, high quality (QY up to 72%) thick shell InP/GaP/ZnS core/shell QDs (12.8 ± 1.4 nm) are synthesized using multiple injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 57 publications
1
19
1
Order By: Relevance
“…After that, the InP/GaP/ZnS QD@SiO 2 nanoparticles were coupled with CRP antibodies as the fluorescent probes for the CRP quantitative detection by the QD-based fluorescence-linked immunosorbent assay (QD-FLISA). At last, the fabricated InP/GaP/ZnS QD@SiO 2 –FLISA exhibited a high sensitivity of 0.9 ng mL –1 for CRP, which was more than a 3.2-fold improvement over those of previously reported PMAH-coated InP/GaP/ZnS QDs and was close to that of state-of-the-art silica-encapsulated Cd-based QDs …”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…After that, the InP/GaP/ZnS QD@SiO 2 nanoparticles were coupled with CRP antibodies as the fluorescent probes for the CRP quantitative detection by the QD-based fluorescence-linked immunosorbent assay (QD-FLISA). At last, the fabricated InP/GaP/ZnS QD@SiO 2 –FLISA exhibited a high sensitivity of 0.9 ng mL –1 for CRP, which was more than a 3.2-fold improvement over those of previously reported PMAH-coated InP/GaP/ZnS QDs and was close to that of state-of-the-art silica-encapsulated Cd-based QDs …”
Section: Introductionsupporting
confidence: 67%
“…The LOD was a ratio of three standard deviations (SDs) of 10 individual measurements to the slope ( K ) of the lowest concentration calibration plot (LOD = 3 SD/ K ), which was a significant parameter for evaluating the sensitivity of the immunoassay. Compared with our previous InP/GaP/ZnS QD@PMAH–FLISA, the key achievement in the InP/GaP/ZnS QD@SiO 2 –FLISA was that the detection sensitivity increased 3.2 times to 0.9 ng mL –1 . This indicated that the SiO 2 shell played a critical role in the high PL QY of InP/GaP/ZnS QD@SiO 2 and the InP/GaP/ZnS QD@SiO 2 with large surface area coupled with more antibodies, both of which had the benefit for improving the detection sensitivity.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations